Edaravone Dexborneol provides neuroprotective effect by inhibiting neurotoxic activation of astrocytes through inhibiting NF-κB signaling in cortical ischemia - Zhe Chen; Tao Li; Hai-Bin Tang; Zi-Wei Lu; Zi-Yi Chen; Zhi-Hong Zhao; Xue-Ling Yang; Li-Li Zhao; Mei-Juan Dang; Ye Li; Wen-Xian Li; Xiao-Juan Wang; et al. (Brain Research Bulletin)
Edaravone Dexborneol (EDB), comprised of edaravone and (+)- bornel, has been demonstrated to have synergistic effects of antioxidant and anti-inflammatory, which makes it to be applied for stroke as a protectant. However, the underlying mechanism of neuroprotection of EDB has not been fully elucidated. Increasing evidence has shown that neurotoxic A1 astrocytes were closely related to neuronal death after cerebral ischemia. However, whether EDB could provide neuroprotection by modulating the activation of astrocytes has not yet been elucidated. The present study aimed to explore whether EDB afforded neuroprotection by modulating A1 polarization of astrocytes and the down-stream signaling after cerebral ischemia. We first validated the neuroprotective effects of EDB in mice suffering focal cerebral ischemia via evaluating behavioral test, infarct volumes and neuronal survival. As for the down-stream signaling, our data further showed that EDB alleviated neuronal death by suppressing activation of neurotoxic A1 astrocytes via inhibition of NF-κB signaling pathway in vitro. Additionally, administration of EDB reduced the number of A1 reactive astrocytes in mice of focal cerebral ischemia. The above findings demonstrated that EDB provided neuroprotective effect by inhibiting neurotoxic activation of A1 astrocytes in animal model of cerebral ischemia, which indicated that EDB-mediated phenotypic regulation of astrocytes is a potential research direction to promote neurological recovery in central nervous system (CNS) diseases.